POTENSI KOMODITAS KOPI DALAM PEREKONOMIAN DAERAH DI KECAMATAN PANGALENGAN KABUPATEN BANDUNG - Dina Fithriyyah; Eliana Wulandari; Tuhpawana P. Sendjaja (Universitas Galuh Ciamis, 2020)
Coffee is one of plantation commodities that plays an important role for Indonesian economy, in which of its benefits is for country income. The strategic role of coffee in Indonesian economy can be observed from contribution of the plantation sub-sector to Indonesia's Gross Domestic Product (GDP), in which coffee is the main plantation commodity. Pangalengan Sub District, Bandung District is one of the arabica coffee centers in West Java. Coffee has a big role to increase Gross Regional Domestic Product (GRDP) in Bandung. This study aims to determine the potential of coffee commodity for economic growth in Bandung, especially in Pangalengan. This research used quantitative descriptive methods using time series data from the production of estate crops in the period of 2012-2016. The analysis used Location Quotient (LQ) and Shift Share. The results of this study indicate that coffee is the main plantation commodity in Pangalengan and Bandung. The shift share analysis shows that coffee has a positive growth both in Pangalengan and Bandung even though the whole production growth in plantation sectors decreased in Bandung.